Even perfect numbers and their Euler's function - Syed Asadulla (International Journal of Mathematics and Mathematical Sciences)
The purpose of this article is to prove some results on even perfect numbers and on their Euler's function. The results obtained are all straightforward deductions from well-known elementary number theory.